2015
DOI: 10.1002/2014jd022497
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the radiation budget with a regional climate model over Europe and inspection of dimming and brightening

Abstract: Shortwave (SW) and longwave (LW) components of the radiation budget at the surface and top of atmosphere (TOA) are evaluated in the regional climate model RegCM version 4 driven by European Centre for Medium-Range Weather Forecasts Reanalysis over Europe. The simulated radiative components were evaluated with those from satellite-based products and reanalysis. At the surface the model overestimated the absorbed solar radiation but was compensated by a greater loss of thermal energy while both SW and LW TOA net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 100 publications
(190 reference statements)
1
21
0
Order By: Relevance
“…Without ARE the simulated trend in SSR is underestimated (0.09 ± 0.14 W m −2 yr −1 ), suggesting that changes in aerosol concentrations are a dominant driver of SSR trends during this period. The simulated positive trend in SSR including ARE presented here is in agreement with other studies over this period Allen et al, 2013;SanchezLorenzo et al, 2013;Chiacchio et al, 2015).…”
Section: Aerosol Optical Depthsupporting
confidence: 92%
See 1 more Smart Citation
“…Without ARE the simulated trend in SSR is underestimated (0.09 ± 0.14 W m −2 yr −1 ), suggesting that changes in aerosol concentrations are a dominant driver of SSR trends during this period. The simulated positive trend in SSR including ARE presented here is in agreement with other studies over this period Allen et al, 2013;SanchezLorenzo et al, 2013;Chiacchio et al, 2015).…”
Section: Aerosol Optical Depthsupporting
confidence: 92%
“…Folini and Wild (2011) performed transient simulations with ECHAM5-HAM over Europe (with interactive aerosols) and found that simulated reductions in SSR occurred too early in the model, whereas the increase in SSR was correctly timed. Using a regional climate model over Europe driven by reanalysis data, Chiacchio et al (2015) overestimated SSR, simulated a premature onset of dimming and demonstrated that only simulations including aerosols were able to reproduce the observed brightening trend. In addition, Koch et al (2011) simulated the correct interdecadal variability in SSR but underestimated the magnitude of observed SSR.…”
Section: S T Turnock Et Al: Modelled and Observed Changes In Europmentioning
confidence: 99%
“…Assessing changes in solar power generation is arguably more difficult due to, among other things, unresolved processes in relatively coarse climate models and uncertain parameterizations (e.g., Chiacchio et al, 2015;Herwehe et al, 2014). Acknowledging this difficulty and associated uncertainties, an evaluation of the EURO-CORDEX data finds limited impacts of climate change on solar photovoltaic (PV) potentials .…”
Section: Introductionmentioning
confidence: 99%
“…The significance of satellite-based solar radiation data for the evaluation of climate models has been recognized over the last few years (e.g., [12][13][14][15]). Compared to global radiation, there are many more stations worldwide that provide sunshine duration measurements.…”
Section: Introductionmentioning
confidence: 99%